PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI (STUDI PERBANDINGAN ANTARA FAKULTAS EKONOMI DAN BISNIS ISLAM DAN FAKULTAS SYARIAH DAN HUKUM UINAM) - Suhartini, Eka (Jurnal Minds: Manajemen Ide dan Inspirasi, 2015)
This study aims to determine 1) Competence influence on employee performance on FEBI UINAM 2) Compare competence and performance of employees between FEBI and FSH UINAM. This study uses quantitative research methods, as well as the study include types of research according to the level of explanation that is associative and comparative. And then involved 36 respondents. Methods of data collection are questionnaires, abservations, interviewa and literature. This study uses data analysis techniques for associative is simple regression whereas the t test for independent comparative. The result of this study that 1) The competence effect on employee performance FEBI UINAM 2)Tthere is a difference between competence and employee performance FEBI and FSH UINAM.